MARKETING MIX MODEL INCREASING SALES VOLUME IN PANDEMI ERA COVID 19: RAFIDA BATIK OF CENTRA BATIK FABRIC INDUSTRY INDONESIA - Adcharina Pratiwi; Suranto Suranto; Nurgiyatna Nurgiyatna; Etika Muslimah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Batik fabric is a product of the creative industry which is a product of micro, small and medium enterprises (SMEs) in the field of handmade. The aim of the study is to raise the potential of batik fabric products, performance marketing mix model so that batik fabric products (batik) able to increase sales volume. The design and construction strategy marketing mix applied to increase sales is through the development of marketing mix approaches 9Ps (products, prices, promotions, distribution, people, physic evidend, process, payment, packaging) to sales volume in pandemi Covid 19. This research is beneficial as a marketing development model of “Batik” fabric products so that the output is used as a source/material in mentoring or guiding marketing for “Batik” fabric entrepreneurs. The method of data analysis through Structural Equation Modelling (SEM) analysis to design models of marketing mix on sales volume.